2020
DOI: 10.1101/2020.07.31.20165126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A longitudinal survey for genome-based identification of SARS-CoV-2 in sewage water in selected lockdown areas of Lahore city, Pakistan; a potential approach for future smart lockdown strategy

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections has affected more than 15 million people and, as of 22 July 2019, caused deaths of more than 0.6 million individuals globally. With the excretion of SARS-CoV-2 in the stool of symptomatic and asymptomatic COVID-19 patients, its genome detection in the sewage water can be used as a powerful epidemiological tool to predict the number of positive cases in a population. This study was conducted to detect SARS-CoV-2 genome in sewage water durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…From March 20 to April 9, 2020, among samples collected from various locations in 17 districts, 21/78 (26.9%) were positive ( Sharif ), and Lahore samples were collected on alternate days between July 13 to 25, 2020. We found that 22/28 (78.6%) of the positive samples ( Yaqub et al, 2020 ) from Wuhan Pulmonary Hospital, China, were collected after the initial identification of 2019-NCoV. Moreover, 4/15 (26.7%) ( Zhang et al, 2020 ) samples collected from Zhongnan Hospital of Wuhan University from January 20 to February 9, 2020, were positive.…”
Section: Occurrence Of Viruses Worldwide In Wastewatermentioning
confidence: 87%
See 2 more Smart Citations
“…From March 20 to April 9, 2020, among samples collected from various locations in 17 districts, 21/78 (26.9%) were positive ( Sharif ), and Lahore samples were collected on alternate days between July 13 to 25, 2020. We found that 22/28 (78.6%) of the positive samples ( Yaqub et al, 2020 ) from Wuhan Pulmonary Hospital, China, were collected after the initial identification of 2019-NCoV. Moreover, 4/15 (26.7%) ( Zhang et al, 2020 ) samples collected from Zhongnan Hospital of Wuhan University from January 20 to February 9, 2020, were positive.…”
Section: Occurrence Of Viruses Worldwide In Wastewatermentioning
confidence: 87%
“…SARS-CoV2 quantitative analysis done by RT-qPCR Filtration & PEG centrifugation ORF1ab Total of 78 untreated wastewater samples analysed 21/78 (26.9%) samples detected positive NA ( $author1$ et al, 18] </id><AuthGrp><Author><in>S.</in><dl> </dl><au>Sharif</au></Author></AuthGrp> ) Various locations Pakistan Lahore Viral RNA genome recovered from concentrated wastewater samples using BSL-3 of IM, UVAS. SARS-CoV2 quantitative analysis done by RT-qPCR Centrifugation (4 °C for 15 minutes) ORF1ab Total of 28 untreated wastewater samples analysed 22/28 (78.6%) samples detected positive 2.67 × 10 2 to 3.60 × 10 4 ( Yaqub et al, 2020 ) ChinaWuhan SARS-CoV2 quantitative analysis done by RT-qPCR NA NA Total of 42 untreated stool samples analysed 28/42 (66.67%) samples detected positive NA ( Chen et al, 2020 ) China SARS-CoV2 quantitative analysis done by RT-qPCR Centrifugation (56 °C for 30 minutes inactivation) ORF1ab Total of 15 untreated stool samples analysed 4/15 (26.7%) samples detected positive 0.05 to 1.87 × 10 5 ( Zhang et al, 2020 ) Wuhan Not Detected = (ND); Not Available = (NA). …”
Section: Virus Detection Methods In Wastewater Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This changed dramatically in February 2020 when COVID-19 had been declared a pandemic. Since then, the sewage testing for fragments of the SARS-CoV-2 has been successfully deployed and proven in value as an early detection tool and employed by public health authorities throughout Europe including Belgium [64], England [65], France [66], Germany [67], Hungary [68], Italy [69], the Netherlands [70], Russia [71], Spain [72,73], Switzerland [74], and Turkey [75,76], The same technique was also employed in other parts of the globe such as Hong Kong [77], Israel [78,79], India [80], Pakistan [81], Saudi Arabia [82], Brazil [83,84], Chile [85], Mexico [86], the USA [87,88] and Australia [89,90].…”
Section: Sewage Testing As a Diagnostic Tool For The Presence Of Sars-cov-2mentioning
confidence: 99%
“…The said study has a major limitation that it relies on conventional Real-time reverse transcriptase (rRT-PCR) method. Moreover, the authors have tested sewage water from only a single source ( Yaqub et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%